Impact of Adjuvant Therapy on Survival in Curatively Resected Gallbladder Carcinoma - Choudhary, Sunil (J Clin Diagn Res, 2015)
BACKGROUND: Gallbladder carcinoma (GBC) has the propensity to fail at loco-regional (LR) and distant sites despite aggressive radical surgery. Adjuvant therapy in the form of radiotherapy (RT), systemic chemotherapy (CT) and chemoradiation (CRT) is the usual practice. Due to rarity of this disease, there is limited evidence to suggest the type of adjuvant treatment which should be offered to the patients. AIM: The study was conducted to evaluate the impact of adjuvant treatment on curatively resected GBC patients. SETTINGS AND DESIGN: Histological proven patients of GBC registered between June, 2008 and July, 2014 were identified from our hospital database and retrospective analysis was done. MATERIALS AND METHODS: Patients of GBC who had curative resection followed by adjuvant treatment as RT alone, CT alone or CRT were included in the study. STATISTICAL ANALYSIS: Adverse prognostic factors and the effect of adjuvant treatment on overall survival (OS) and disease free survival (DFS) were evaluated using Cox Regression Method and Kaplan Meier plot. RESULTS: We identified 33 patients of which 23 were Stage I or II disease (Early disease) and the remaining 10 were Stage III or IV disease (Advanced disease). All except one patient had adenocarcinoma. A total of 5 patients were treated with RT alone while 16 patients received CT alone. The remaining 12 patients were treated with CRT. Median follow-up period was 8.5 months. At analysis 4 were alive while the remaining 29 were dead due to disease. With regard to “Early disease” patients who had RT alone, CT alone and CRT, the median OS was 22.3, 10.3 and 15.2 months respectively (p = .440). Cohort of patients with “Advanced disease” who were treated with CT alone and CRT the median OS was 7.5 and 7.0 months respectively (p = .643). On multivariate analysis none of the prognostic factors had an adverse impact on survival. CONCLUSION: The impact of adjuvant treatment in the form of RT, CT or CRT after curative resection in GBC patients was seen in terms of improved survival but was not statistically significant.